Harmonization of Transport Charging in Slovak Republic - Čarný, Štefan; Zitrický, Vladislav; Šipuš, Denis (LOGI - scientific journal on transport and logistics, 2020)
Inland transport in European Union is facing difficult but fundamental goals to achieve. Most of them are more accurately described in the White Paper on the future of Europe. By signing the Treaty of Lisbon, every European country is obligated to fulfil the legislation of the European Parliament. The main document dealing with the transport issue and ecological aspect of transport is the White Paper, which serves as a fundamental document for establishing the legislation and standards. The European Parliament legislation must be implemented in the national legislation including e. g. regulations, decisions or recommendations of the European Parliament. The legislation based on the White Paper is closely focused on transport and the related ecological aspect. Conclusions of this document lead decisions of EU to take serious actions in many different sectors. The transport sector has a significant impact on our environment and the future of the European Union. The current main goal of transport sector is to achieve reduction in emitting pollutants in our environment, and smoothly transfer to renewable sources of energy or at least trying to minimize the resources per transport performance unit.